Freezing in halide salts - Akdere, Ue.; Yilmaz, M.; Kavanoz, H. B.; Tasseven, C. (POLISH ACAD SCIENCES INST PHYSICS, 2008)
The static criterion that the amplitude of the principal peak of the liquid structure factor has a constant value along the freezing line and the onset of freezing are studied from the structure factors and the static dielectric functions of halide salts interacting via the effective pair potentials through the hypernetted-chain approximation. It is observed that the criterion above is restricted to the effective charge difference. The critical value of plasma parameter at freezing is affected by the mobility and number concentration of anions and cations. The distribution of the value of the static dielectric function closest to the wave number axis in the negative region is also determined by the charge difference and the ordering of ions and related to the onset of freezing.
Keywords: ONE-COMPONENT PLASMA; STATIC DIELECTRIC FUNCTION; ALKALI-HALIDES; ALPHA-AGI; MOLTEN; DYNAMICS; CRITERION; EQUATION; LIQUIDS; PHASE; Physics